Patients’ Experiences of Nurses’ Heartfelt Hospitality as Caring: A Qualitative Approach - Kelly, R; Wright-St Clair, V; Holroyd, E (Wiley, 2018)
Aims and Objectives The aim of this study was to answer the question “What is the lived experience of hospitality during a patient’s hospital stay for elective surgery?” Background Hospitality centres on a host offering comfort to others, as in a personal care context. Caring constitutes the essence of what it is to be human, having a profound effect on wellbeing and recovery from surgery. Caring is one of the most elusive and diversely contested concepts in nursing, however, care provided by nurses seldom transcends as deep human connections and social utility. This study explored the nature, meaning and experience of hospitality as care from the perspective of elective surgery patients. Design A hermeneutic phenomenological methodology. Methods Data were gathered through semi-structured, face to face interviews with seven patients from both private and public hospitals, and from different cultural backgrounds. Results Three interpretative notions were: experiences of hospitality as feeling “really” cared for, being at ease and being healed. Hospitality exists in the receiver’s lived experience, evoking a special moment which leads to feelings of great comfort and feelings of being truly cared about. When hospitality is received patients feel a connection, they begin to trust and their healing begins. Conclusion The offering of often small, yet heartfelt acts of hospitality, indicated that nurses can evoke powerful lived experiences which benefit patients undergoing elective surgery.
Keywords: Hospital Care; Caring; Nursing Education; Patients' Experiences; Phenomenology; Surgery; Qualitative